Physiotherapy approaches applied to patients with fibromyalgia: systematic review of clinical trials - Pinheiro, Yago Tavares; Souza, Marcelo Cardoso de; Araújo, Thiago Anderson Brito de; Silva, Rodrigo Scattone da; Lins, Caio Alano de Almeida (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Due to the complexity of the fibromyalgic patient’s condition, therapeutic resources are being recruited to manage the signs and symptoms of patients with this disorder. However, the range of options offered hinders the decision-making of therapists, since the approaches are often heterogeneous. Objectives: The objective was to characterize publications on the effects of physical therapy in patients with fibromyalgia and to investigate the main effects of these therapies. Methods: A search was performed between November 2017 and March 2018 by articles published in the databases PEDro, PUBMED and SciELO from the combination of the descriptors “Fibromyalgia” and “Physical Therapy Modalities”. We included clinical trials involving subjects with fibromyalgia and that approached some physiotherapeutic technique in at least one of the intervention groups. Results: A total of 861 studies were identified. Of these, 28 met the eligibility criteria. In addition, 02 studies were included from secondary sources. There was a predominance of studies published in the last nine years, in which the evaluation instruments of the type questionnaires, inventories and scales were used mainly. In addition, it was possible to observe an improvement in outcomes such as pain, quality of life, sleep, general health, functional capacity, balance, anxiety and depression in patients with Fibromyalgia submitted to techniques such as kinesiotherapy, hydrotherapy, electrothermo-therapy, bandages, among others. Conclusions: The evidences found support the use of physiotherapy as a therapeutic resource for patients with Fibromyalgia, since the techniques studied were beneficial in almost all cases. Record PROSPERO: CRD42018087432.